Functional and sensory evaluation of bread made from wheat flour fortified with wine byproducts - Muñoz-Bernal, Oscar A.; de la Rosa, Laura A.; Martinez Ruiz, Nina Del Rocio; Rodrigo Garcia, Joaquin; Alvarez-Parrilla, Emilio; Coria-Oliveros, Alma J.; Subiría-Cueto, Carlos Rodrigo; Reyes-Vega, María de la Luz; Vazquez-Flores, Alma Angélica (2024)
Grape pomace is the main byproduct of the wine industry and an important source of dietary fiber and phenolic compounds. Grape pomace powder (GPP) partially substituted 8, 10, 12, 15, and 25% of the wheat flour in bread formulations. The proximate composition, total dietary fiber content, phenolic compounds, texture profile, color, and bioaccessibility of phenolic compounds in vitro were measured in the bread. Bread sensory acceptance by consumers was determined using a 9-point hedonic scale. Compared with the control bread (CB), the 8% GPB-substituted bread presented the best results and exhibited an increase in total protein content (7.5%) and total dietary fiber content (6.1%). The total phenolic content was greater in GPB (5.1 mg GAE/g) than in CB (2.1 mg GAE/g). Adding GPP to the bread affected the color, and the color of the GPB-treated bread was darker than that of the CB-treated bread. Still, no significant differences were detected regarding the texture profile or consumer sensory acceptance between the GPB-treated and CB-treated bread. The in vitro analysis of phenolic compound bioaccessibility revealed no differences between the two samples during gastrointestinal digestion. GPP is an interesting byproduct that can be used in bakery. The replacement of 8% of the bread with GPP increased the nutritional content of the bread, particularly the protein, total dietary fiber, and total phenolic content, without affecting the texture or sensory acceptance of the bread. To understand the possible beneficial effect of GPB on consumers, further research on the bioavailability of phenolic compounds and the impact of dietary fiber increment needs to be assessed.